Gabapentin and pregabalin exposures reported to United States poison centers, 2012-2022 - Emily J.R. Carter; Natalie I. Rine; Sandhya Kistamgari; Hannah L. Hays; Henry A. Spiller; Jingzhen Yang; Motao Zhu; Gary A. Smith (BMC, 2024)
Abstract Background Gabapentin and pregabalin were originally introduced as anticonvulsant medications but are now also prescribed on- and off-label for multiple medical disorders, especially for pain management. The national opioid crisis has led to increased use of non-opioid pain medications, including gabapentinoids, which has been associated with changing patterns of adverse events associated with these medications. This study investigated the characteristics and trends of gabapentin and pregabalin exposures reported to US poison centers from 2012 to 2022. Methods National Poison Data System data involving gabapentin and pregabalin exposures for 2012 to 2022 were analyzed. Results There were 124,161 exposures involving gabapentin and pregabalin as the primary substance reported to US poison centers during the study period. Most exposures involved gabapentin (85.9%), females (59.4%), single-substance exposures (62.9%), or occurred at a residence (97.2%). Suspected suicides accounted for 45.2% of exposures. Most exposures were associated with a minor effect (27.4%) or no effect (34.0%), while 22.1% experienced a serious medical outcome, including 96 fatalities. The rate of gabapentin and pregabalin exposures per one million US population increased by 236.1% from 22.7 in 2012 to 76.5 in 2019 (P < 0.001), followed by a non-significant decrease to 68.5 in 2022 (P = 0.068). Conclusions The rate of gabapentin and pregabalin exposures reported to US poison centers increased by more than 230% from 2012 to 2019 before plateauing from 2019 to 2022. The observed rate trend was driven primarily by gabapentin exposures and by cases associated with suspected suicide. Although most exposures were associated with a minor or no effect, 22% of individuals experienced a serious medical outcome, including 96 fatalities. These findings contribute to the discussion of rescheduling gabapentin as a federally controlled substance, which is the current status of pregabalin. Prevention of suicide associated with gabapentin and pregabalin merits special attention.